(NdUHOWN)QÆSTX Æ ZDOROW(B'(NQ (B:s)E (NNAW^ALXNO(B-(NMETODI^NIJ POS)QÆBNIK (B/s)E - (NoRVEHOWSXKA(B, (NwALENTINA mIHAJL)QÆWNA(B,s)E ((NkI)QÇW (B:s)E (Nmediana(B,s, 2004)
(Nw POS)QÆBNIKU ROZGLQNUTO DUHOWNO(B-(NMORALXNÆ PRI^INI WINIKNENNQ ZAHWOR@WANX(B, (N[LQHI OZDOROWLENNQ NA OSNOWÆ PRINCIPÆW OZDOROW^OGO MISLENNQ(B, (NZASOBÆW PSIHÆ^NOÇ SAMOREGULQCÆÇ(B.s)E
(NoRIG)QÆNAL ZAPISU ZA POSILANNQMs)E
Keywords: (NzDOROW(B'(NQs -- (NdUHOWN)QÆSTXs)E; (NL@DINAs; )QÆ(NNDIWÆDUALXNÆSTXs)E; (NOSOBIST)QÆSTXs)E; (NDUHOWN)QÆSTXs)E; (NDUHOWN)QÆ PRINCIPIs)E; (NZDOROW(B'(NQs; (NTEMPERAMENTs; (NMISLENNQs; (NPSIH)QÆ^NA SAMOREGULQCÆQs)E; (NSP)QÆLKUWANNQs)E; (NEMOC)QÆÇs)E; (NKONFL)QÆKTs)E; (NSTRESs; (NPODOLANNQ NEGATIWNIH EMOC)QÆJs)E